The impact of pre-transplant valganciclovir on early cytomegalovirus reactivation after allogeneic hematopoietic stem cell transplantation. (August 2014) - Wilhelm, Kaci; Chemaly, Roy; Saliba, Rima; Gulbis, Alison; Saunders, Ila; Cool, Rita; Ferguson, Jill; Westmoreland, Michael; Rondon, Gabriela; Kebriaei, Partow
Cytomegalovirus reactivation is a common complication of allogeneic hematopoietic stem cell transplant. The use of pre-transplant valganciclovir during the conditioning regimen followed by preemptive therapy has been used in an attempt to reduce the rate of early cytomegalovirus reactivation, but efficacy data are lacking. In this retrospective study, we evaluated the impact of pre-transplant valganciclovir during the conditioning regimen followed by a preemptive approach on the rate of early cytomegalovirus reactivation through day 100. The rate of cytomegalovirus reactivation through day 100 was 41% in the no-valganciclovir group compared to 46% in the valganciclovir group ( p  = 0.4). Interestingly, median time to cytomegalovirus reactivation was earlier in the no-valganciclovir group compared to the valganciclovir group (26 vs. 34 days; p =  0.008) and there was a trend toward a higher rate of cytomegalovirus disease through day 100 in the no-valganciclovir group (0.7% valganciclovir vs. 4% no-valganciclovir; p  = 0.1). Day 100 survival was similar between the groups (90% valganciclovir vs. 91% no-valganciclovir; p  = 0.8). Although the time to cytomegalovirus reactivation is significantly longer in the valganciclovir group, this did not impact the rate of cytomegalovirus reactivation or survival by day 100 suggesting that other strategies need to be explored.